Identification of chromoblastomycosis agents by PCR based reverse line blot (PCR-RLB) hybridization assay. (December 2018) - Najafzadeh, M.J.; Gerrits van den Ende, A.H.G.; Vicente, V.A.; Dolatabadi, S.; Sun, J.; de Hoog, G.S.
Abstract: Chromoblastomycosis is one of the most prevalent implantation fungal infections caused by melanized fungi, affecting individuals with certain risk factors with high morbidity due to its recalcitrant nature. It is difficult to identify the etiological agents and thus a suitable reproductive molecular identification method applicable in developing countries has been investigated. We report the identification of four different fungal causative agents of chromoblastomycosis by reverse line blotting hybridization (RLB) based on biotin-labeled PCR products and amine labeled probes to hybridize. Sixty five reference strains, including type strains, i.e. Fonsecaea pedrosoi, F. monophora, F. nubica, and Phialophora verrucosa, obtained from the CBS-KNAW were included in this study. Internal transcribed spacer 1 (ITS1) regions of relevant species were aligned and adjusted using BIONUMERICS v. 4.61 in order to design four specific probes to identify informative nucleotide polymorphisms. The final identification of these species by RLB assay was concordant with ITS sequencing and showed 100% specificity with no cross hybridization, able to identify all tested strains. The time and cost were less compare to other routine identification methods such as sequencing. This assay allows sensitive and specific simultaneous detection and identification of a different fungal species.